Coping Strategies in Overcoming Loneliness of Out-of-Town Students - Halimah; Imroatun Nafia; Saiful Muktiali; Listian Indriyani Achmad (Aqlamuna: Journal of Educational Studies, 2024)
Loneliness is a psychological challenge often experienced by out-of-town university students. Being far from family, they often feel isolated and struggle to adapt to a new environment. This study aims to analyze the experiences of loneliness among students at FIKT, Pelita Bangsa University, including its causes and coping strategies. This research employs a qualitative phenomenological approach, involving 90 students through questionnaiers and unstructured interviews. The findings indicate that loneliness is caused by physical and emotional distance from family, a lack of meaningful activities, and difficulties in building social connections. Loneliness affects students moods, learning motivation, and physical health. Coping Strategies include engaging in productive activities, building social relationships and seeking support from campus communities. Positive social interactions and the role of the campus environment are key factors in overcoming loneliness. Social students psychological well-being.